Quality of life in children and adolescents after treatment for acute lymphoblastic leukemia according to the NOPHO ALL2008 protocol - Mogensen, Nina (John Wiley & Sons, 2025)
Background: The improved outcome of childhood acute lymphoblastic leukemia (ALL) over the last decades has increased the importance of assessing late effects and health-related quality of life (HRQoL), particularly when evaluating and comparing outcomes in clinical trials. This study aimed to assess HRQoL in children treated for ALL according to the NOPHO ALL2008 protocol.
Procedure: Children, aged 1 to less than 18 years at diagnosis, alive in first remission, and their parents, were asked to complete PedsQL 4.0 Generic Core Scales (self- and proxy-report) at ≥6 months after end of therapy. Data on socioeconomic factors and parent-reported toxicity were collected through a study-specific questionnaire, and the NOPHO ALL2008 database was used to identify eligible families and add additional disease- and treatment-related data. HRQoL data were collected during 2013-2019 in Sweden, Finland, and Denmark.
Results: A total of 299 children were included. The older children (8 years and older) reported similar HRQoL scores compared to Finnish reference data, except lower scores for School Functioning in high-risk patients. Scores from the parent-proxy and self-reports from 5-7-year olds were notably lower than reference. Parent-reported toxicity was associated with lower total and physical HRQoL scores in adjusted models for younger as well as older children in the self-report and parent-proxy versions, and also with lower psychosocial score in the parent-proxy.
Conclusions: Self-reported HRQoL was similar to reference population. The most important determinant for HRQoL after end of ALL treatment was parent-reported toxicity during treatment. Thus, minimizing complications is an obvious focus for future treatment protocols.